UPAYA MENINGKATKAN PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK DENGAN BERMAIN LOMPAT DAN LONCAT PADA SISWA SD - Reza Maenadi; Lalu Sapta Wijaya Kusuma; Rindawan Rindawan (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
ABSTRACT Low student engagement and the suboptimal mastery of fundamental squat-style long jump skills in elementary schools indicate a gap between the objectives of physical education and actual classroom practices. This study aims to improve the quality of both the learning process and outcomes through the implementation of a contextually designed play-based approach. The research employed a classroom action research design conducted in two cycles involving fifth-grade students of SD Negeri 2 Sambelia in the 2022/2023 academic year. Each cycle consisted of planning, action, observation, and reflection stages, with data collected through observation, interviews, and documentation. Data were analyzed using descriptive qualitative and quantitative techniques based on percentages to identify changes in learning outcomes and student engagement. The results revealed a consistent improvement in fundamental movement skills, particularly in the phases of approach, take-off, and landing, accompanied by increased active participation during the learning process. The play-based approach, combined with variations of jumping and hopping activities, created a more interactive and adaptive learning environment suited to students’ characteristics. Furthermore, there was a notable improvement in instructional quality from the first to the second cycle, as indicated by the predominance of students achieving good performance levels. In conclusion, the play-based approach has proven effective in enhancing both learning outcomes and student engagement. These findings highlight that the integration of structured play activities can serve as an innovative and relevant strategy in elementary physical education. ABSTRAK Rendahnya keterlibatan siswa dan belum optimalnya penguasaan keterampilan dasar lompat jauh gaya jongkok di sekolah dasar menunjukkan adanya kesenjangan antara tujuan pembelajaran pendidikan jasmani dan praktik di lapangan. Penelitian ini bertujuan untuk meningkatkan kualitas proses dan hasil pembelajaran melalui penerapan pendekatan bermain yang dirancang secara kontekstual. Penelitian menggunakan pendekatan classroom action research yang dilaksanakan dalam dua siklus pada siswa kelas V SD Negeri 2 Sambelia tahun ajaran 2022/2023. Setiap siklus meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi, dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan teknik deskriptif kualitatif dan kuantitatif berbasis persentase untuk melihat perubahan hasil belajar dan keaktifan siswa. Hasil penelitian menunjukkan adanya peningkatan yang konsisten pada keterampilan gerak dasar, terutama pada aspek awalan, tolakan, dan pendaratan, disertai peningkatan partisipasi aktif siswa selama pembelajaran. Pendekatan bermain yang dikombinasikan dengan variasi aktivitas lompat dan loncat mampu menciptakan suasana belajar yang lebih interaktif dan adaptif terhadap karakteristik siswa. Selain itu, terjadi perbaikan kualitas pembelajaran dari siklus pertama ke siklus kedua yang ditandai dengan dominasi capaian kategori baik. Dengan demikian, pendekatan berbasis permainan terbukti efektif dalam meningkatkan hasil belajar sekaligus keterlibatan siswa. Temuan ini menegaskan bahwa integrasi aktivitas bermain yang terstruktur dapat menjadi strategi inovatif dan relevan dalam pembelajaran pendidikan jasmani di sekolah dasar.